Reliability and Validity of the Educational Stress Scale for Adolescents (ESSA) in a Sample of Greek Students - Evangelia Moustaka; Flora Bacopoulou; Kyriaki Manousou; Christina Kanaka-Gantenbein; George P. Chrousos; Christina Darviri (MDPI AG, 2023)
This research outlines the initial validation of a new instrument to quantify academic stress, the Educational Stress Scale for Adolescents (ESSA). A total of 399 students (61.9% females, 38.1% males), with a mean age of 16.3 years, participated in the research protocol. Cronbach's α for the total 16-item ESSA scale was 0.878, suggesting good reliability. Cronbach's α for each one of the five components were statistically positively significant. The Greek version of the Educational Stress Scale for Adolescents (ESSA) can be utilized as a valid tool to measure the perceived educational stress in adolescents.